Penyusunan Profil Kampung Akrilik Di Kecamatan Padang Utara - Dinda Djesmedi; Fitri Firdalius; Rasmita Rasmita (STMIK Royal, 2022)
Abstract: Acrylic Village in North Padang District is one of the thematic villages in Padang City which is located in KB RW Village. 12 Berok Gunung Pangilun, Gunung Pangilun Village, Padang City. This Acrylic Village is a knitted thematic village that produces handicrafts, such as knitted bags, flower vases, tissue boxes and others. Acrylic Village is still in the development stage. Currently, the Acrylic Village does not yet have a profile in the form of books and videos, so to find out about this Acrylic Village, the resource persons must repeat the history, handicrafts, and others. The writing team will create a profile for Acrylic Village to help introduce it to the wider community. The author uses the method of interview, observation and library research. In order to introduce this Acrylic Village, the author made a book and profile video to be used as a more effective information medium so as to provide information about Acrylic Village and make it a center for promoting creative economy products. Keywords: arcylic; thematic villages; profile Abstrak: Kampung Akrilik di Kecamatan Padang Utara merupakan salah satu kampung tematik yang ada di Kota Padang yang berada di Kampung KB RW. 12 Berok Gunung Pangilun, Kelurahan Gunung Pangilun Kota Padang. Kampung Akrilik ini merupakan kampung tematik rajutan penghasil kerajinan tangan, seperti tas rajutan, vas bunga, kotak tisu dan lainnya. Kampung Akrilik masih dalam tahap pengembangan. Saat ini Kampung Akrilik belum mempunyai profil dalam bentuk buku dan video, sehingga untuk mengetahui tentang Kampung Akrilik ini narasumber harus mengulang menyampaikan sejarah, hasil kerajinan, dan lainnya. Tim penulis akan membuat profil untuk Kampung Akrilik supaya membantu memperkenalkan ke masyarakan luas. Penulis menggunakan metode wawancara, obervasi dan penelitian kepustakaan. Dalam rangka memperkenalkan Kampung Akrilik ini penulis membuat buku dan video profil untuk dijadikan media informasi yang lebih efektif sehingga memberikan informasi tentang Kampung Akrilik dan menjadikan sentra promosi produk ekonomi kreatif. Kata Kunci: akrilik; kampung tematik; profil